If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(2) + 9x + -7 = 0 Reorder the terms for easier multiplication: 2 * 2x + 9x + -7 = 0 Multiply 2 * 2 4x + 9x + -7 = 0 Reorder the terms: -7 + 4x + 9x = 0 Combine like terms: 4x + 9x = 13x -7 + 13x = 0 Solving -7 + 13x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 13x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 13x = 0 + 7 13x = 0 + 7 Combine like terms: 0 + 7 = 7 13x = 7 Divide each side by '13'. x = 0.5384615385 Simplifying x = 0.5384615385
| 6x^2+19x=-10 | | 5(4m-7)(m-4)=0 | | 8.5+9.4= | | 6y+8=5y-8 | | 2x=45-4x | | 24x-6x(13x-9)=-13-13x(6x-1) | | -9x+15=-22-14(x+12) | | (r+2)2=0 | | 14.75+1x=50 | | 3x(2x-1)-6x(7+x)=90 | | 4t^3-3t=0 | | 16y^2-18y-9=0 | | x^2-15x-216=0 | | 9x^3+45x^2-25x-125=0 | | .5(2y-1)-(.5-.2y)+1=0 | | x+6-5x=180 | | 5=-(2+6t)-t | | 7x+4x-6x=8x | | (3x+2)(5x^2-16x+12)=0 | | 59=50+(n-40)/4 | | 4(5x+4)=24(x-1) | | 2z+3=76 | | 5x-8=13++7(x-3) | | -11=14-2h | | 4(5y-2)+3(2y+6)=25(3y+2)-19y | | 3(3z+3)=5z-7 | | a^2+11a-126=0 | | 15c^2=48+48c | | 8x^2-55x-7= | | 6x^2-5xy+y^2= | | 2x-100=5x-100 | | 4x^3-24x^2-x+36=0 |